We find the front everywhere: grievability and the proximity of social and anonymous death in Doris Salcedo’s “Plegaria Muda”. - DiSarno, Jamie (Mortality, 2024)
In Plegaria Muda (2008, ‘silent prayer’), Colombian sculptor, Doris Salcedo amassed 166 elongated tables. Stacked in pairs with soil inbetween, the sheer number evokes a mass grave. However, here, the installation impedes free movement through the exhibition space. Viewers are left without the capacity to ignore the work’s presence. Salcedo was influenced by violence in Los Angeles where the war on drugs disproportionately affected African Americans and Latinos. Concurrently in Colombia, the ‘false positives’ controversy where the Colombian state compensated the Army for “guerrilla deaths,” or more accurately the extrajudicial killings of poor civilians. Here, I aim to historicise Plegaria Muda. Attending to these histories of state violence demonstrates precisely how Salcedo’s works suggest that distance cannot easily be placed between the United States with its presupposed moral authority and events elsewhere in the world. Namely, proximity in Salcedo’s works challenge a defensive estrangement the global north might put in place against violence in the global south. In Plegaria Muda, Salcedo connected the social death of marginalised neighbourhoods in Los Angeles A with the anonymous and invisible death of Colombia’s marginalised poor. Salcedo’s installation asks viewers to examine which bodies are, in Judith Butler’s terms, ‘ungrievable’ from the start.